The Influence of Intellectual Intelligence and Emotional Intelligence on Employee Performance - Tira Feniawati; Ani Yunaningsih (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Human Resource is a vital asset for the organization to achieve its goals and one of the important factors to achieve the organizational goals is performance. To produce optimal performance, it is necessary to have an adequate quality of the human resources, not only in terms of intelligence and the ability to think (intellectual intelligence), emotional intelligence also needed to control and manage themselves. Intellectual intelligence and emotional intelligence are important because they greatly influence the performance. The purpose of this study is to analyze the magnitude of the influence of intellectual and emotional intelligence on employee performance. The method that will use in this research is the census method which this research takes the whole employee’s population of KPID Provinsi Jawa Barat to become respondents. The research instrument uses questionnaires with data analysis techniques using: instrument test (validity and reliability), and multiple linear regression analysis. The results showed that the magnitude of the effect of intellectual intelligence and emotional intelligence on employee performance of 85.1% and the rest of 14.9%. Partially emotional intelligence greater influence on employee performance.